Distributed Video Coding: an overview of basics, research issues and solutions. (25th May 2012) - Ji, Wen; Chen, Min; Park, James J.; Xiong, Naixue; Chen, Yiqiang
Distributed Video Coding (DVC) is an emerging eld that offers a brand–new paradigm for answering challenging questions in video coding applications. The unique potentials of DVC lie in its particular structure, targeting low encoding complexity and error robustness. DVC shows good prospects especially in wireless video sensor network, video monitoring, mobile camera, satellitic video communication and the other energy supply limited video applications. There has been amount of activities both in research and industry. Following the evolving stages, this paper provides an overview of DVC, including the theoretical foundation: Slepian–Wolf Theorem and Wyner–Ziv Theorem, the framework foundation: Distributed Source Coding (DSC) and the relation between DSC and DVC, and unique technologies comparison to conventional compressed method, including side information, channel coding, joint decoding and motion estimation, which highlight critical research issues. Additionally, ve representative encoder are introduced as implementation aspects. Finally, several active research areas in the state of the art are reviewed with open challenging issues.